Face Rejuvenation: a new combinated protocol for biorevitalization - Brandi, Cesare; Cuomo, Roberto; Nisi, Giuseppe; Grimaldi, Luca; D'Aniello, Carlo (Acta Biomedica Atenei Parmensis, 2018)
Introduction: The slowing of the aging process is subject of great research and attention in modern society, particularly aging of face. Processes involved are very complex. Mesotherapy. hyaluronic acid and carbon dioxide injection can be used for biorevitalization and skin rejuvenation. Methods: Three groups were made and 62 patients were enrolled. Patients with superficial wrinkles of the face, neck and/or décolleté, without presence of nasolabial folds and marionette wrinkles were included in group 1. Patients with superficial/medium depth wrinkles of the face, neck and/or décolleté, with moderate nasolabial folds but no marionette wrinkles were included in group 2. Patients with deep wrinkles of the face, with deep nasolabial folds and marionette wrinkles were included in group 3. Patients were treated with three different protocols that included injections of amino acids, vitamins and hyaluronic acid in association with carbon dioxide injection. We submitted the PAIS and GAIS scales and we analyzed the scores obtained with Wilcoxon’s and Kolmogorov-Smirnov’s tests. Statistical Product and Service Solutions (SPSS) softare was used. The p-value was considered acceptable if inferior to 0,05 (p>0,05). Results: In according with these tests, the differences of values at one week and at the end of the study are significant (p<0,05) for both PAIS and GAIS. No side effects were reported. Conclusions: Protocol treatment used in this study gave statistically valid results in the rejuvenation of face for mild, moderate and severe aging.